2022
DOI: 10.1136/jnis-2022-019447
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-driven ASPECTS for the detection of early stroke changes in non-contrast CT: a systematic review and meta-analysis

Abstract: BackgroundRecent advances in machine learning have enabled development of the automated Alberta Stroke Program Early CT Score (ASPECTS) prediction algorithms using non-contrast enhanced computed tomography (NCCT) scans. The applicability of automated ASPECTS in daily clinical practice is yet to be established. The objective of this meta-analysis was to directly compare the performance of automated and manual ASPECTS predictions in recognizing early stroke changes on NCCT.MethodsThe MEDLINE, Scopus, and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…A recent meta-analysis compared the performance of automated and manual ASPECTS predictions for early stroke changes. It reported good reliability between reference standards and both expert (ICC 0.62 [95% CI 0.52 to 0.71]) and automated predictions (ICC 0.72 [95% CI 0.61 to 0.80]), while concluding that automated prediction may be superior, based on higher ICC values 23. The ICC in our study was 0.78 [95% CI: 0.73 to 0.82] showing good-to-excellent agreement, with results comparable to the meta-analysis 23.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent meta-analysis compared the performance of automated and manual ASPECTS predictions for early stroke changes. It reported good reliability between reference standards and both expert (ICC 0.62 [95% CI 0.52 to 0.71]) and automated predictions (ICC 0.72 [95% CI 0.61 to 0.80]), while concluding that automated prediction may be superior, based on higher ICC values 23. The ICC in our study was 0.78 [95% CI: 0.73 to 0.82] showing good-to-excellent agreement, with results comparable to the meta-analysis 23.…”
Section: Discussionmentioning
confidence: 95%
“…It reported good reliability between reference standards and both expert (ICC 0.62 [95% CI 0.52 to 0.71]) and automated predictions (ICC 0.72 [95% CI 0.61 to 0.80]), while concluding that automated prediction may be superior, based on higher ICC values 23. The ICC in our study was 0.78 [95% CI: 0.73 to 0.82] showing good-to-excellent agreement, with results comparable to the meta-analysis 23. In clinical situations, however, ASPECTS is often used in a dichotomized fashion, for selection of patients for reperfusion treatments.…”
Section: Discussionmentioning
confidence: 95%
“…An AI model outperformed expert readers in detecting early ischemic changes on NCCT in a recent study, 75 and a systematic review including 11 studies and 1976 cases revealed that AI-based ASPECTS performed similar or better than radiologists in identifying early stroke changes on NCCT. 76 Moreover, AI-based NCCT-ASPECTS was reported as good or better as human rating for posterior circulation stroke. 77 However, the accuracy and reliability of AI- and human-based NCCT-ASPECTS depends on time from stroke onset to imaging and is lower in hyperacute stroke and fast stroke progressors.…”
Section: Optimization Of Imaging Technologymentioning
confidence: 99%
“…Emerging AI technologies may offer more rapid identification of these patients. For instance, AI approaches to detect stroke and the lesion core from noncontrast computed tomography scans are currently being investigated 69 and may accelerate the identification of patients eligible for recanalization therapies. AI stroke diagnosis could be applied in primary and secondary centers and may work autonomously.…”
Section: Reperfusionmentioning
confidence: 99%